(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the specifics of the formation of immunity against "mass culture" in adolescent students on the basis of a gender approach, thinking that adolescence is a complex, controversial period, the development of self-awareness and self-esteem during this period.